Design and actualisation of the improved Jakes fading channel. Issue 3 (1st February 2017) - Liang, Kuo‐hsien; Lo, Jenn‐Yuan; Weng, Wan‐de
Abstract : Based on the original Jakes model, the authors have proposed a new design for an inexpensive fading channel simulator that can be easily actualised with fewer low‐frequency oscillators than that used in existing structures. The major modifications from the original Jakes model include the generation of path gains under an improved distribution, and presetting the arrival angles and initial phases to be zero. These modifications not only reduce the hardware cost of the channel simulator, but also provide better statistic properties than the model proposed by Zheng and Xiao. Specifically, the improved Jakes fading channel model presented in this study needs only eight low‐frequency oscillators. Simulation results have demonstrated that the proposed design exhibits improved first‐order and second‐order statistical properties.